Design and Evaluation of a Consequent Pole K-Shaped Permanent Magnet Motor for Outboard Application using a Hybrid Mathematical Model - Mehrage Ghods; Jawad Faiz; Hamed Gorginpour (CES Transactions on Electrical Machines and Systems)
Nowadays, there is considerable research interest in proposing modern permanent magnet (PM) electric machine structures for applications such as electric vehicles. Several radial and axial topologies with different arrangements of PM in the stator and rotor have been introduced for PM Vernier motors (PMVM) with the aim of increasing the performance characteristics such as power factor, efficiency, rotational torque, torque density and wider constant torque-speed region. Meanwhile, the spoke PM arrangement has provided higher torque density than the surface and V-shaped arrangement. But in contrast, the V-shaped arrangement has a more sinusoidal flux and less cogging torque. In this paper, a 620 W, 12-slot 16-pole Vernier PM motor with a fractional slot arrangement. Consequent K-shaped pole is introduced, which has the advantages of spoke and V-shaped magnetic arrangements. After presenting and confirming the concept of the proposed structure based on functional comparison with conventional structures, an analytical modeling based on the harmonic analysis method is introduced to accurately predict the performance of the machine, and finally the proposed structure is prototyped and the experimental results are simulated and modeling are compared.